Measuring society's temporal synchronization via days of importance. (November 2019) - Vihalemm, Triin; Harro-Loit, Halliki
This article approaches public holidays, anniversaries and other days of importance as temporal synchronization mechanisms of society through generating pauses and interrupting the routines and schedules of the daily lives of large groups of people. The authors explain the possibilities of the empirical measurement of the synchronization of pauses in society via sociological surveys, by asking about the personal celebration of particular days of importance and about celebration activities. The authors introduce two possible measurement methods of the pause synchronizing effect of days of importance. The first method is based on the people who celebrate a particular day of importance and the differences in the celebration across socio-demographic groups in society. The second method is based on the activities of celebration: how many people perform a particular activity and how socio-demographically differentiated the performance of that particular activity is. The authors also explain the framework for selecting days of importance based on different layers of the Gregorian calendar and the framework for categorizing celebration activities based on the estimation of the scope of the pause and interruption of daily routine they create. The methods are demonstrated based on the case of Estonian society and its calendar of days of importance, and the results of empirical analysis and discussion are considered in light of the desynchronization thesis of late modern societies and the disintegration of societies into temporal ghettos.